The Influence of Work Environment, Work Discipline, and Teamwork on Employee Performance (Case Study at Sambi District Office, Boyolali Regency) - Dodik Khoirul Anam; Sri Wijiastuti; Zandra Dwanita Widodo (ProBisnis : Jurnal Manajemen, 2025)
Human resources (HR) play a crucial role in determining the success of organizational activities, including in government institutions such as the Sambi District Office, Boyolali Regency. This study aims to analyze the influence of the work environment, work discipline, and teamwork on employee performance at the Sambi District Office. This research employed a quantitative descriptive method with a saturated sample of 35 employees. Data were collected through questionnaires, observation, and documentation, and analyzed using classical assumption tests, multiple linear regression, t-tests, and the coefficient of determination. The findings indicate that a conducive work environment characterized by adequate lighting, comfortable temperature, cleanliness, and minimal noise significantly improves employee performance. Work discipline, reflected in punctuality, adherence to rules, and low absenteeism, also has a positive and significant effect on performance. Furthermore, teamwork contributes favorably by enhancing coordination, communication, and shared responsibility in completing tasks. The results of the coefficient of determination show that the three variables simultaneously influence employee performance by 48.2%, while the remaining 51.8% is affected by other factors outside this study. These findings highlight the importance of strengthening the work environment, discipline, and teamwork to improve the quality of public services and support organizational effectiveness at the district level.